PENGARUH PEMBERIAN AGRICARIVIT TERHADAP HISTOPATOLOGI HATI DAN GINJAL AYAM BROILER - , TIA SETIABUDI, Dr. drh. Syarifuddin Tato, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Giving Agricarivit supplement on broilers are expected can improve the carcass production because broiler has good genetics in it. The new problem that arises is supplements are not used properly can damage the liver and kidneys of chicken. The damages of liver and kidneys feared can inhibit the metabolism of chemicals or toxins to be excreted out of the body and it could be bad manifestation for consumers of broiler chickens. The way to research this problem is giving the supplement to the chicken groups of treatment with different doses to determine its effect on the liver and kidney of chicken. This research is expected to provide an overview Agricarivit influence as a supplement to the damages of chicken liver and kidney. This research used 12 broilers (Day Old Chicks) were divided into a control group, the treatment one dose (2 gram/L), the treatment two doses (4 gram/L) and the treatment three doses (6 gram/L). Agricarivit was given in drinking water on schedule. Necropsy performed after 35th day for examination of liver and kidney microscopically. The results of this research indicate that administration of doses exceeding Agricarivit supplement triggers damages of liver and kidney chicken. In livers are commonly found necrosis.